Brainstorming the cryoplane layout by using the iterative AHP-QFD-AHP approach. Issue 2 (3rd April 2017) - Ucler, Caglar
Abstract: Most of commercial civil aircraft are derivatives of each other. They start with an aero-structural design based on the mission profile, and what remains is the integration of existing subsystems. This only leaves room for incremental innovation. When a totally new concept has to be worked out, an innovative brainstorming procedure has to be facilitated, leading to a new product definition. This collaborative creative thinking is not an easy task, and analytical design management tools are required. Therefore, an iterative AHP-QFD-AHP approach for brainstorming is implemented into a concurrent engineering environment in the early phases of layout conception. In the case study, the proposed model delivered the product definition of the cryoplane concept successfully, which promises clean operation.